PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP LOYALITAS PELANGGAN TEH BOTOL SOSRO (Studi Kasus Pada Konsumen Teh Botol Sosro yang Melakukan Pembelian di Indomaret Kelurahan Tembalang) - Zenia Perwitasari; Agus Hermani DS (Jurnal Ilmu Administrasi Bisnis, 2018)
PT. Sinar Sosro manufactures ready-to-drink tea beverages called Teh Botol Sosro. Teh Botol Sosro has been widely consumed by the public and became the market leader of ready-to-drink tea beverages in Indonesia in 2013-2016 according to Top Brand Index (TBI), but the percentage of people who consume Teh Botol Sosro in Indonesia is declining year by year. This is due to the increasing number of emerging competitors by providing better quality and lower prices thus making people switch to consume competitors product. This research aims to determine how the influence given by product quality and price to Teh Botol Sosro customer loyalty. This type of research is an explanatory type with the help of questionnaire and interview as the tools in collecting data. The amount of the sample used in this research is 100 respondents who ever made a purchase of Teh Botol Sosro at Indomaret located in Tembalang Village. Methods of data analysis used is test validity and reliability, the correlation coefficient (R), regression test, the coefficient of determination (R2 ), the significance of the t-test and F-test. The result of this research shows that product quality and price severally has significant, strong enough and positive influence toward customer loyalty. Two variables have been tested gradually or even together show that product quality (0,613) and price (0,522) simultaneously have strong enough relation with customer loyalty. The amount of contribution owned by product quality is greater than price, coefficient of determination value (R²) for quality product is 37,6% and price is 27,3%. The suggestion in this research is the company can improve the quality of its products related to the suitability of taste variation, durability, and health and safety of Teh Botol Sosro to be consumed, so it could maintain the product quality. The company also suggested to lowered the price of Teh Botol Sosro to be lower than other brands of packaged tea and other types of beverages so the price set is cheaper than the competitor and able to dominate the market again.